Saint`s triade with diverticulosis of jejunum – rare variety of the syndrome - A. S. Benian; M. P. Ayrapetova; M. A. Medvedchikov-Ardiia; S. A. Mukhambetaliev (Вестник хирургии имени И.И. Грекова)
The objective was to present the case report of the patient with rare clinical finding – Saint`s triade. The examination diagnosed giant paraesophageal hernia (III type) with gastric torsion and cholelithiasis. The 72-years old woman was admitted to hospital with complaints of acute dysphagia. During the laparotomy operation, jejunal diverticulosis was also detected. The patient underwent crural repair, fundoplication, and cholecystectomy. The postoperative period was uneventful. She was discharged on the 14th day after surgery with recovery. The features of the presented case were the prevalence of the clinical picture of complicated hiatal hernia and the localization of diverticula in the jejunum. The clinical significance of the Saint`s triade was to assess the probability of this combination in identifying one of the components.